Robotic, laparoscopic and open surgery for gastric cancer compared on surgical, clinical and oncological outcomes: a multi-institutional chart review. A study protocol of the International study group on Minimally Invasive surgery for GASTRIc Cancer—IMIGASTRIC. Issue 10 (19th October 2015) - Desiderio, Jacopo; Jiang, Zhi-Wei; Nguyen, Ninh T; Zhang, Shu; Reim, Daniel; Alimoglu, Orhan; Azagra, Juan-Santiago; Yu, Pei-Wu; Coburn, Natalie G; Qi, Feng; Jackson, Patrick G; Zang, Lu; et al.
Abstract : Introduction: Gastric cancer represents a great challenge for healthcare providers and requires a multidisciplinary treatment approach in which surgery plays a major role. Minimally invasive surgery has been progressively developed, first with the advent of laparoscopy and recently with the spread of robotic surgery, but a number of issues are currently being debated, including the limitations in performing an effective extended lymph node dissection, the real advantages of robotic systems, the role of laparoscopy for Advanced Gastric Cancer, the reproducibility of a total intracorporeal technique and the oncological results achievable during long-term follow-up. Methods and analysis: A multi-institutional international database will be established to evaluate the role of robotic, laparoscopic and open approaches in gastric cancer, comprising of information regarding surgical, clinical and oncological features. A chart review will be conducted to enter data of participants with gastric cancer, previously treated at the participating institutions. The database is the first of its kind, through an international electronic submission system and a HIPPA protected real time data repository from high volume gastric cancer centres. Ethics and dissemination: This study is conducted in compliance with ethical principles originating from the Helsinki Declaration, within the guidelines of Good Clinical Practice and relevant laws/regulations. A multicentre study with a large number of patients will permit further investigation of the safety and efficacy as well as the long-term outcomes of robotic, laparoscopic and open approaches for the management of gastric cancer. Trial registration number: NCT02325453; Pre-results.